Motivational Interviewing to Address Vaccine Hesitancy: Insights from an Intervention in Portugal - Mendonça,Joana (2024)
Abstract Research, to date, suggests the need for healthcare professionals to adapt their communication style to the needs and characteristics of parents when discussing childhood vaccination. Motivational interviewing (MI) has been recognized as an important communication style, based on a patient-centred model of care, leading to the responsibility and motivation to change in cases of vaccine hesitancy. The current study intended to assess the attainment of MI competencies by healthcare professionals in Portugal who may interact with vaccine-hesitant parents. The pre- and post-training survey results showed a significant increase in the participants’ scores in all three pre-defined dimensions: acquisition of knowledge, perception of skills application, and sense of confidence. Our results suggest that integrating MI training into healthcare professionals’ curriculum appears to be a promising avenue to pursue to foster their immunization-related communication skills in Portugal and elsewhere.